Two novel species of subgenus Russula crown clade (Russulales, Basidiomycota) from China - Yu Song; Xiu-Chao Xie; Bart Buyck (European Journal of Taxonomy, 2021)
Two novel species of Russula (Russulaceae, Russulales), R. coronaspora Y.Song sp. nov. and R. minor Y.Song sp. nov. belonging to subgenus Russula crown clade, are described based on both morphological and phylogenetic evidence. In morphology, R. coronaspora sp. nov. is mainly characterized by its distinct spores ornamented with sparse, cylindrical and isolated spines, which resemble coronavirus, and gelatinized pileipellis with pileocystidia mostly septate and sometimes branched; R. minor sp. nov. possesses a very small basidiocarp with pileus less than 2.5 cm in diameter., small basidia, easily peeling and gelatinized pileipellis with slender terminal cells and abundant SV+ pileocystidia. Positions of the two new species in both phylogenetic trees based on ITS and 5-locus sequences (nLSU, mtSSU, rpb1, rpb2 and tef1) confirm their distinct taxonomic status.